MATHEMATICAL MODELS OF SPECIFIC CREEP DEFORMATION OF CONCRETE - Maia Tchanturia; Nino Nakvetauri; Fatima Verulashvili (Scientific Research and Experimental Development, 2025)
Creep deformation of concrete is one of the important factors in the theory of calculation of reinforced concrete structures. In calculations, it appears as a creep characteristic, which is a function of the product of two quantities: the creep value and the modulus of elasticity. These quantities were obtained experimentally, so they have random deviations from a fixed value. This article presents a statistical study of one of these quantities - specific creep deformation. To determine the boundaries of possible deviations of the creep characteristic of concrete, it is necessary to statistically process the data of numerous experiments conducted by a number of scientists under various experimental conditions. To be able to properly apply them in a statistical experiment, a mathematical model was first built to eliminate these errors. To check the reliability of the constructed mathematical model, a statistical experiment was conducted, namely, for the data obtained by the formula, a statistical distribution order and a theoretical distribution law were built, the reliability of which was checked using the Pearson and Kolmogorov correlation criteria. The reliability of the constructed mathematical model was confirmed with a fairly high probability.